Heat transfer enhancement in flow boiling using environmentally safe additives. Issue 1 (31st December 2016) - Gajghate, Sameer S.; Khandekar, Vaibhav; Chopade, Shrikrushna
Abstract: This study represents experimental data for flow boiling. Experiments were conducted over the horizontal and angular section with inner heating element with the downward flow. Bubble dynamics & heat transfer enhancement in flow boiling using saturated water and betel nut solution has been studied experimentally. The concentration of surfactant was taken 400–1, 200 ppm. Bubble behavior is observed for different angle of water tube as a nucleation site. The bubble dynamics was studied using SONY Cyber-shot camera operating at 30 frames per second at atmospheric pressure. The result obtained by aqueous solution with and without additives shows dissimilarity between temperature difference, heat fluxes & heat transfer coefficient. The upstream interface of the bubble is found to exhibit both forward and reverse movement during bubble growth. The little effect of gravity on the bubble growth rate by the heater glass tube inclination. The enhancement is observed due to surface tension of the environment accepted additive solution.